New Perspectives on the Aberrant Alveolar Repair of Idiopathic Pulmonary Fibrosis - Wang, Zhao Ni; Tang, Xiao Xiao (Frontiers in Cell and Developmental Biology, 2020)
Idiopathic pulmonary fibrosis (IPF) is a chronic lung disease of unknown etiology and high mortality. Current therapeutic strategies have limited efficacy and the prognosis remains poor. Based on the histological observations of IPF lung tissues and experimental studies using lung fibrosis animal models, it is gradually accepted that impaired epithelial regeneration after lung injury is a critical mechanism underlying the pathogenesis of pulmonary fibrosis. The central role of AEC2 in this process has been well-elucidated, while the contribution of other lung progenitor/stem cells is less discussed. Recently, increasing studies have identified several non-AEC2 epithelial progenitor/stem cells with great plasticity to transform into mature AECs and reconstitute alveolar epithelium after lung injury. However, why these cells did not function as the “back-up” stem cells to regenerate alveolar epithelium in IPF is still unknown. In this review, we discuss the contribution of lung epithelial progenitor/stem cells in the aberrant alveolar regeneration, and provide a novel perspective on the mechanism of IPF pathogenesis, in which non-AEC2 progenitors might play an essential role.